Hidden Action, Identification, and Organization Design - Wendelin Schnedler (University of Heidelberg, Department of Economics, 2010)
Incentives often fail in inducing economic agents to engage in a desirable activity; implementability is restricted. What restricts implementability? When does re-organization help to overcome this restriction? This paper shows that any restriction of implementability is caused by an identifi cation problem. It also describes organizations that can solve this identifi cation problem and provides conditions under which such organisations exist. Applying the findings to established and new moral hazard models yields insights into optimal organization design, uncovers the reason why certain organization designs, such as advocacy or specialization, overcome restricted implementability, and formalizes a wide-spread type of multi-tasking problem.
urn:nbn:de:bsz:16-opus-112481
Keywords: 330; moral hazard; hidden action; implementation; multi-tasking; identification by organization design; Leistungsanreiz; Produktionstheorie; Moral Hazard; Persönlichkeitspsychologie; Organisatorischer Wandel; Theorie